2014
DOI: 10.3168/jds.2013-7503
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of genetic parameters for productive life, reproduction, and milk-production traits in US dairy goats

Abstract: Heritabilities and correlations for milk yield (MY), fat yield (FY), protein yield (PY), combined fat and protein yield (FPY), fat percentage (F%), protein percentage (P%), age at first kidding (AFK), interval between the first and second kidding (KI), and real and functional productive life at 72mo (FPL72) of 33,725 US dairy goats, were estimated using animal models. Productive life was defined as the total days in production until 72mo of age (PL72) for goats having the opportunity to express the trait. Func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 48 publications
1
32
2
Order By: Relevance
“…Their estimates were in the range of 0.04-0.35 for milk yield and 0.02-0.18 for fat yield. In addition, positive and lower genetics correlation estimates of functional productive life and milk yield (0.33) and fat yield (0.23) have been reported in US dairy goats (Castañeda-Bustos et al 2014). On the other hand, Fuerst-Waltl et al (2013) reported unfavourable correlations between milk yield and LPL in both extensive (−0.159) and intensive (−0.192) management systems in Austrian Fleckvieh (dual-purpose Simmental).…”
Section: Resultsmentioning
confidence: 99%
“…Their estimates were in the range of 0.04-0.35 for milk yield and 0.02-0.18 for fat yield. In addition, positive and lower genetics correlation estimates of functional productive life and milk yield (0.33) and fat yield (0.23) have been reported in US dairy goats (Castañeda-Bustos et al 2014). On the other hand, Fuerst-Waltl et al (2013) reported unfavourable correlations between milk yield and LPL in both extensive (−0.159) and intensive (−0.192) management systems in Austrian Fleckvieh (dual-purpose Simmental).…”
Section: Resultsmentioning
confidence: 99%
“…Heritabilities of production traits Heritability for MY520 was within the expected range for this population, based on a random regression analysis on a larger sample of the present population (Mucha et al, 2014) and in line with estimates for dairy ewes and goats (El Saied et al, 2005;Rupp et al, 2011;García-Peniche et al, 2012;Castañeda-Bustos et al, 2014). Heritability for DIMLife was similar to that estimated by Torrero (2010;0.13), and lower The absolute number of weeks of first kidding relative to peak kidding season, as defined by the 4 weeks of the year where the greatest number of kids are born.…”
Section: Discussionmentioning
confidence: 97%
“…This result was in agreement of some literature stated that age of first kidding in goats ranged between 321-534 days including local and exotic breed (Sutama et al 2011;Patel & Pandey 2013;Budisatria & Udo 2013;Bhowmik et al 2014;Dereje et al 2015). The pooled data of Saanen, Toggenburg, Anglo Nubian and La Mancha in USA dairy goats showed that age of first kidding was 507.97 days (Castañeda-Bustos et al 2014).…”
Section: Reproductive Characteristicsmentioning
confidence: 99%